Myeloid Sarcomas Causing Unilateral Cranial Nerve Palsies in a Patient with Relapsed Acute Myeloblastic Leukemia - A. Mendez-Hernandez; X. A. Andrade; S. Upadhyay; L. M. Parra-Rodriguez; E. Caldeira; L. H. Paz; H. Mann; M. Zia; L. Sumoza (Case Reports in Hematology)
Myeloid sarcomas (MS) are a rare manifestation of myeloid malignancies and can often be misdiagnosed, leading to a delay in treatment. The objective of this clinical case is to highlight the challenges of the clinical presentation and to emphasize the importance of this manifestation ensuring timely diagnosis and therapy. Here, we present a 43-year-old man who was diagnosed with acute myeloblastic leukemia (AML) after being evaluated for unintentional weight loss, subcutaneous nodules, thrombocytopenia, and anemia. The patient underwent chemotherapy with complete remission and presented 4 months later with dysphagia and cranial nerve palsies. Appropriate imaging and biopsy led to a diagnosis of myeloid sarcoma, and a decision was made to begin reinduction chemotherapy for AML achieving a second complete remission although his neurological deficits did not improve. Our case illustrates the protean presentation of myeloid sarcomas; clinicians should have a high suspicion for MS and remain vigilant when unexplained signs and symptoms arise in the background of a myeloid malignancy although challenges still remain when presentation is de novo. Advancements in understanding the pathophysiology of MS have been performed but remain not completely understood. High clinical suspicion, appropriate imaging, biopsy techniques, and expertise are paramount for timely diagnosis and treatment.